Prevalence and factors associated with smartphone addiction among adolescents-a nationwide study in Malaysia - Lee, Kai Wei; Ching, Siew Mooi; Ali, Norsiah; Ooi, Chor Yau; Sidek, Shahnul Kamal; Amat, Azlin; Yatim, Yusnita; Yahaya, Zaiton; Shamsuddin, Nabihah; Ibrahim, Idora; Abdul Majid, Fauzia; Othman, Fazlin Suhana; et al. (Tech Science Press, 2023)
Smartphone ownership among adolescents is getting common in this decade especially in Malaysia; Adolescent are strongly devoted to their smartphone and this may lead to smartphone addiction. Studies have reported that smartphone addiction has become an emerging social and health problem especially among the youth in many countries however there is lack of study among adolescents in Malaysia. This study aimed to examine the prevalence and factors associated with smartphone addiction among adolescents in Malaysia. This was a cross-sectional study involving adolescents from 15 primary care clinics throughout the country. Respondents were assessed on their smartphone activities using the Malaysian short version of the Smartphone addiction scale (SAS-M-SV). Multiple logistic regression was used to determine the predictors of smartphone addiction among adolescents. The study was conducted among 921 adolescents with 49.6 male (n = 457). The mean age of adolescents was 16.4 ± 2.4 years. The ethnicity distribution were 74.6 Malay, 7.3 Chinese, 4.7 Indian and 13.4 other ethnicities. The prevalence of smartphone addiction was 37.1 (342/921); 37.4 in male and 36.9 in female. Based on multiple logistic regression analysis, longer duration of smartphone use per week was associated with higher odds of smartphone addiction among adolescent (odd ratio = 1.005, 95 confidence interval = 1.000–1.009, p-value = 0.039). Smartphone addiction is present in nearly four in ten adolescents in Malaysia. Adolescents who spend longer duration in smartphone usage per week were associated with higher odds of having smartphone addiction. Parents should be more alert and vigilant about this finding. Hence, parents should limit their children from spending too much of time with smartphone in order to prevent their children from getting smartphone addiction.